PORTAL INFORMASI PELAYANAN CALON JAMAAH HAJI BERBASIS WEB PADA KEMENTERIAN AGAMA KABUPATEN SAMBAS - Nurbaiti; Widji Astuti, Theresia; Lena, Sonty (Jurnal Sistem Informasi (JASISFO), 2022)
The Ministry of Religion of the Sambas Regency is a Vertical Agency of the Ministry of Religion domiciled in the Regency. One of the tasks of the Ministry of Religion of Sambas Regency is to provide services, guidance and guidance in the field of Hajj and Umrah. For services at the Ministry of Religion of Sambas Regency to prospective pilgrims, it is still not effective and efficient. The method used is Prototype with the stages of collecting requirements, building prototyping, evaluating prototyping, coding the system, testing the system, evaluating the system, and using the system. The Web-Based Information Portal for Prospective Hajj Pilgrims Services at the Ministry of Religion of Sambas Regency is built with functionalities according to user needs, namely: information on the schedule of Hajj rituals, information on Hajj travel schedules, information on estimated Hajj departures, information on material for Hajj rituals, information on data for prospective pilgrims, information health data of prospective pilgrims, message information and report information.